El Nino and World Primary Commodity Prices : Warm Water or Hot Air? - Brunner, Allan (IMF Working Papers; Working Paper ;, 2000)
This paper examines the historical effects of the El Nino-Southern Oscillation (ENSO) cycle on world prices and economic activity. The analysis indicates that ENSO has economically-important and statistically-significant effects on world real commodity prices. A one-standard-deviation positive surprise in ENSO, for example, raises real commodity price inflation about 3-1/2 to 4 percentage points. Moreover, ENSO appears to account for almost 20 percent of commodity price inflation movements over the past several years. ENSO also has some explanatory power for world consumer price inflation and world economic activity, accounting for about 10 to 20 percent of movements in those variables.